METHODS FOR OBTAINING A COORDINATION COMPOUND OF NICKEL (II)-NITRATE WITH INDOLE ACETIC ACID AND STUDYING THEIR BIOLOGICAL PROPERTIES - B. Sapayev; F.E. Saitkulov; Kh.M. Nasimov; U. Qalandarov; K.A. Zakhidov (Scholar Express Journals, 2022)
The method of obtaining has been studied methods for obtaining a coordination compound of nickel nitrate with indole acetic acid and studying their biological properties, biologic activity of different varieties of cotton was studied.
Keywords: The method; coordination compound; nickel nitrate; indole acetic acid